Childhood and literature (XXI Century. Spanish Literature and Culture, 2012)
Authors of childhood memories often reject first- person linear narrative by changing the chronological order of events, by  introducing flash-backs,  by linking events of similar thematic content, by altering the narrative viewpoint etc.. This essay tries to explain the reasons why these changes take place and ultimately, the very goal of childhood recollections which is the need to return to a state of innocent nakedness, the paradise lost of our infancy. According to this essayist, the discourse of childhood reminiscence is directed  both to the child´s eye-witness accounts as to the self-analysis of the adult writer of these accounts.
Keywords: memory; autobiography; eye-witness accounts; self-analysis; Esperanza Ortega